Phase Formation in the Ti-Y-O System Formed Using High-Energy Methods; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Ivanov Yu. F. Yuriy Fedorovich; Petrikova E. A.; Teresov A. D.; Klopotov A. A.; Gromov V. E.; Budovskikh E. A.; Kalashnikov M. P. Mark Petrovich; Klopotov V. D. Vladimir Dmitrievich (Material Engineering and Technologies, 2015)
Title screen